Dietary supplementation of solubles from shredded, steam-exploded pine particles modulates cecal microbiome composition in broiler chickens - Ncho, Chris Major; Goel, Akshat; Gupta, Vaishali; Jeong, Chae-Mi; Jung, Ji-Young; Ha, Si-Young; Yang, Jae-Kyung; Choi, Yang-Ho (Journal of animal science and technology, 2023)
This study evaluated the effects of supplementing solubles from shredded, steam-exploded pine particles (SSPP) on growth performances, plasma biochemicals, and microbial composition in broilers. The birds were reared for 28 days and fed basal diets with or without the inclusion of SSPP from 8 days old. There were a total of three dietary treatments supplemented with 0% (0% SSPP), 0.1% (0.1% SSPP) and 0.4% (0.4% SSPP) SSPP in basal diets. Supplementation of SSPP did not significantly affect growth or plasma biochemicals, but there was a clear indication of diet-induced microbial shifts. Beta-diversity analysis revealed SSPP supplementation-related clustering (ANOSIM: = 0.31, < 0.01), with an overall lower (PERMDISP: < 0.05) individual dispersion in comparison to the control group. In addition, the proportions of the were increased, and the relative abundances of the families Vallitaleaceae, Defluviitaleaceae, Clostridiaceae, and the genera and ( < 0.05) were significantly higher in the 0.4% SSPP group than in the control group. Furthermore, the linear discriminant analysis effect size (LEfSe) also showed that beneficial bacteria such as and were identified as microbial biomarkers of dietary SSPP inclusion ( < 0.05; | LDA effect size | > 2.0). Finally, network analysis showed that strong positive correlations were established among microbial species belonging to the class , whereas and were mostly negatively correlated with . Taken together, the results suggested that SSPP supplementation modulates the cecal microbial composition of broilers toward a "healthier" profile.